RELATIONSHIP PRODUCT QUALITY AND PRICE WITH CONSUMER BUYING INTEREST IN OLE-OLE FUTSAL BUNG TOMO SURABAYA - Ahedi Syukro Sahudi; I Nyoman Sudapet; Hamzah Denny Subagyo (NAROTAMA UNIVERSITY, Indonesia, 2019)
This research was conducted with the aim of knowing the relationship between product quality and price with the interest of buying consumer Ole-Ole Futsal Bung Tomo. This type of research uses a quantitative approach. The sample in this study were 30 respondents taken by the snowball effect method. The data analysis technique in this study usedcorrelation test analysis Spearman rank. The calculation process was aided by theapplication program Statistical Package for the Social Sciences (IBM SPSS Statistics 20). The results of this study indicate that a correlation of 0.877 means that it is very strong and based on calculations, the product quality variable with consumer buying interest has a sig value of 0.000 <0.05, so Ho is rejected, the product quality is significantly associated with consumer buying interest. And the price variable shows that there is a correlation of 0.738 which means strong and based on calculations, the price variable with consumer buying interest has a sig value of 0.000 < 0.05 so Ho is rejected, then the price is significantly associated with consumer buying interest.